(untitled) (The NOUN Journal of Agricultural Research and Development (NJARD), 2025)
trials were conducted during 2020 rainy season at Birnin Kudu Local Government (11°21’ 48.4”N, 9°52’ 35.3”E) and Jikas area in Maruta ward under Gwaram Local Government (11°28’ 16.4”N, 9°27’ 33.2”E). Both sites were located in Jigawa State and fall within Sudan Savannah agro ecological zone of Nigeria; The experiment evaluated the performance of pearl millet as affected by intra row spacing and nitrogen levels. The treatments consisted of three intra row spacing (25, 50 and 75cm) and four nitrogen levels (0, 40, 80 and 120kg N/ha). The treatments were factorally combined and laid out in a randomized complete block design and replicated three times. Panicle diameter, panicle weight, Stover yield, 1000 grains weight, grain yield and harvest index were observed as yield characters. Results revealed that, intra-row spacing had significant (P<0.05) effect on panicle diameter, panicle weight, stover yield, 1000 grains weight and grain yield. The interaction between the intra-row spacing and nitrogen fertilizer application was statistically significant (P<0.05) on panicle diameter, panicle weight, Stover yield, 1000 seeds weight and grain yield. From this study, it could be concluded that an intra-row spacing of 75cm combined with application of 120kgN/ha may be recommended to farmers in the study area, as such would be beneficial to improve the production of pearl millet.